2014
DOI: 10.1890/12-1628.1
|View full text |Cite
|
Sign up to set email alerts
|

How wide is a stream? Spatial extent of the potential “stream signature” in terrestrial food webs using meta‐analysis

Abstract: The magnitude of cross-ecosystem resource subsidies is increasingly well recognized; however, less is known about the distance these subsidies travel into the recipient landscape. In streams and rivers, this distance can delimit the "biological stream width," complementary to hydro-geomorphic measures (e.g., channel banks) that have typically defined stream ecosystem boundaries. In this study we used meta-analysis to define a "stream signature" on land that relates the stream-to-land subsidy to distance. The 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
177
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(188 citation statements)
references
References 38 publications
7
177
0
Order By: Relevance
“…After emergence, amphibians and aquatic insects are expected to be unevenly distributed in surrounding terrestrial landscapes, with the highest abundances likely to occur near the water (Sabo and Hagen 2012;Bartrons et al 2013;Muehlbauer et al 2014;Dreyer et al 2015). Our data from a set of 16 lakes in the Klamath Mountains confirmed this pattern -aquatic insect biomass was inversely proportional to distance from the lake shore, with a power law best describing the distribution (K.L.…”
Section: Amphibian and Aquatic Insect Emergence: Flux Estimates And Ssupporting
confidence: 65%
“…After emergence, amphibians and aquatic insects are expected to be unevenly distributed in surrounding terrestrial landscapes, with the highest abundances likely to occur near the water (Sabo and Hagen 2012;Bartrons et al 2013;Muehlbauer et al 2014;Dreyer et al 2015). Our data from a set of 16 lakes in the Klamath Mountains confirmed this pattern -aquatic insect biomass was inversely proportional to distance from the lake shore, with a power law best describing the distribution (K.L.…”
Section: Amphibian and Aquatic Insect Emergence: Flux Estimates And Ssupporting
confidence: 65%
“…The presence of artificial light adjacent to water bodies may affect the distance that organisms move away from the water and therefore the spatial scale of the aquatic-terrestrial subsidy signature in a river landscape (Perkin et al, 2011;Gurnell et al, 2016). A recent review found the density of aquatic insects was reduced by 50% within the first 1.5 m from the water's edge (Muehlbauer et al, 2014). Our traps were located 3 m from the water and collected 85-fold more aquatic insects compared to unlit controls.…”
Section: Flying Insectsmentioning
confidence: 94%
“…The transfer of aquatic resource subsidies into terrestrial food webs via the winged adult stages of aquatic insects is recognized as a key component in the functioning of riverine networks (Moldenke and Linden 2007;Lamberti et al 2010;Muehlbauer et al 2014). Not only do aquatic insects often emerge with very high abundance and biomass, but they also carry nutrients and essential lipids produced within aquatic environments (Baxter et al 2005;Gratton et al 2008;Gladyshev et al 2009;Torres-Ruiz and Wehr 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The potential for land use effects on the composition of aquatic invertebrate communities to alter the composition of dispersal related traits is seen in research by Muehlbauer et al (2014), who found that greater stream-to-land subsidy distances were partly explained by the presence of longer lived and/or stronger flying taxa. Similarly, Carlson et al (2016) found that dispersal distances of adult aquatic insects were longer when abundances of blood-feeding taxa (which disperse widely in search of food) were higher, although the bulk of variation in dispersal distances was explained by characteristics of the terrestrial abiotic environment (wind, insolation etc).…”
Section: Introductionmentioning
confidence: 99%